Selfish User Network Optimization With Celluler Network Traffic Management Model Using Lingo 13.0 - Indrawati Indrawati; Fitri Maya Puspita; Bela Olivia Mareta Silaen; Evi Yuliza; Oki Dwipurwani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2020)
This paper discusses the management of traffic between cloud-based cellular networks. Welldesigned traffic management will allow network operators to draw maximum value from availablecapacity where cloud-based traffic management is called the UE (User Equipment). Runningtraffic management on the side of the UE allows decision making in the UE. Users can reach theQoS level to increase the speed of data received and communication latency or reduce theirpower consumption. Each UE maximizes their utility function, which is modelled based on theQoS parameters, selfishly, at the network side. So, the attempt is to maximize fairness among alluses’ flows by designing new improved model of traffic management cloud based of pricinginternet involving the energy consumption. Also in this paper parameters β as UE parameter valueand α as range value parameter are used. The results show that the improved model is betterthan the original one proposed by previous research in terms of maximum value reached althoughit takes more time for improved model to complete the iterations.